EFEKTIVITAS LATIHAN KEKUATAN OTOT LENGAN TERHADAP KETEPATAN MEMANAH DI EKSTRAKURIKULER PANAHAN SISWA SMK NEGERI 3 LUBUKLINGGAU - Benny Marza Sugara; Sukasno Sukasno; Azizil Fikri (LP4MK STKIP PGRI Lubuklinggau, 2022)
This study aims to determine student learning outcomes after the implementation of push up, dumbbell, and planks arm muscle strength exercises. The type of research used is quasi-experimental. The population of archery extracurricular students at SMK Negeri 3 Lubuklinggau is 20 students and the sample taken is 20 students. For sampling using the Census technique. Data collection using test techniques. The data collected after being analyzed using the z-test at a significant level = 0.05 obtained z_count = 8.73 z_table = 1.64 so that it can be concluded that the accuracy of archery at SMK Negeri 3 Lubuklinggau after the implementation of Arm Muscle Strength Training is significantly in the good category with an average value of students' archery accuracy results of 72.6.